Targeted treatment for erythrodermic psoriasis: rationale and recent advances - Shao, Shuai (Drugs, 2020)
Erythrodermic psoriasis (EP) is an extreme and often refractory variant of psoriasis with high morbidity and increased mortality, and is frequently classified as dermatological emergency. The pathophysiology of EP is largely unknown but is thought to differ from that of plaque psoriasis. Treatment of EP is challenging, and usually based on clinical experience and patient comorbidities, due to its low incidence and limited clinical evidence. Conventional treatments, such as topical glucocorticoid therapy, cyclosporin, acitretin, and methotrexate have some but limited efficacy in EP, and treatment discontinuation may result in flares. Newer biological drugs, including anti-TNF, anti-IL-17, and anti-IL-12/23 agents have shown promise in therapeutic management of EP, but most of the available evidence is currently based on small case series and reports. Few studies have compared available treatment options for EP, and further clinical studies are necessary to provide clinical data and optimal treatment guidelines for EP patients. Here, we provide a comprehensive review of the background of EP, assess the available clinical data on the efficacy of targeted therapies, and aim to provide a foundation for clinical decision making for this rare form of psoriasis.